Metabolic pathways of flobufen-a new antirheumatic and antiarthritic drug. Interspecies comparison - Kvasnicková, E; Szotáková, B; Wsól, V; Trejtnar, F; Skálová, L; Hais, I M; Kuchar, M; Poppová, M (Experimental and toxicologic pathology, 1999)
Metabolic transformations of flobufen, [4-(2',4'-difluoro-biphenyl-4-y1)-4-oxo-2-methylbutanoic acid], a non-steroid antiinflammatory agent, were studied in vitro using the following biological models and species: rat and mouse liver homogenates and liver subcellular fractions (5 000 g and 100 000 g supernatant, mitochondria); rat, mouse, rabbit, guinea-pig and mini-pig liver microsomes; isolated rat hepatocytes; perfused rat liver and 5000 g rat muscle tissue supernatant. Reduced flobufen [4-(2',4'-difluorobiphenyl-4-yl)-4-hydroxy-2-methylbutanoic acid] is the major metabolite generated by the subcellular fractions (in the mild acidic extraction conditions during subsequent laboratory processing is converted to its lactone form). It was detected upon the incubation of flobufen with liver microsomes isolated from all the animals tested. Maximum yield of reduced flobufen in experiments with rat and mouse liver microsomes was found after anaerobic incubation with NADPH. This finding combined with the knowledge of subcellular distribution of enzymes suggest that metabolite formation depends on the activity of microsomal reductases and, probably, also on the activity of the important microsomal reductase, cytochrome P-450. Another flobufen metabolite, arylacetic acid [(2',4'-difluorobiphenyl-4-yl)ethanoic acid], is generated from the reduced metabolite by the cleavage of its side chain, and was detected in isolated hepatocytes - it was the only metabolite found in urine and faeces upon oral administration of the drug. All these metabolites were identified and quantified.
Keywords: Liver; Subcellular Fractions; Animals; antiflogistika nesteroidní; Rabbits; butyráty; Rats, Wistar; játra; subcelulární frakce; druhová specificita; Butyrates; Mice; Species Specificity; NAD; myši; jaterní mikrozomy; morčata; Anti-Inflammatory Agents, Non-Steroidal; Male; Mice, Inbred ICR; Microsomes, Liver; krysa rodu Rattus; myši inbrední ICR; Guinea Pigs; NADP; králíci; zvířata; mužské pohlaví; Rats; potkani Wistar